Lexical-morphological contrast of two varieties of QIIA Yungay: Laraos and Lincha - Cariat Fernández, Karen Belén (2021)
The present research work constitutes a lexical-morphological contrast of two varieties of Yauyos Quechua (Laraos and Lincha: northern and southern Yauyos, respectively) and the consequent reevaluation of their affiliation to the central QIIA group.  The objective is to contrast morphological features of the Lincha and Laraos dialects in order to evaluate their affiliation to the QII. Likewise, the aim is to determine the tendency they show at the lexical level. For this purpose, the data presented by Taylor (1984) and Shimelman (2017) were taken into account, in addition to various stories of the Quechua variants of Laraos and Lincha, compiled by the same authors. The results of this research show that the morphological characterization and lexical repertoire of Yauyos dialects are related to, but not determined by, geographic proximity to a QI or QII subset.